Pola Perjalanan Digital Wisata Gastronomi Berdasarkan Perilaku Wisatawan di Kabupaten Purworejo - Astuti, Fera Widi; Turgarini, Dewii; Pratama, Armandha Redo (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
The decline in the number of tourist visits in 2020 has made the Regional Government of Purworejo Regency strive to increase tourism in Purworejo Regency again. These efforts can be realized by increasing the typical food of Purworejo Regency through gastronomic tourism, considering that there are still many tourists who do not know the typical food of Purworejo Regency and gastronomic tourism has not been developed in Purworejo Regency, so that the development of typical food of Purworejo Regency can be used as a tourist destination for gastronomic tourism. This study uses a qualitative method that collects interviews, observations, documentation, and questionnaires. The results of this study are dawet ireng, clorot, kue lompong, and geblek can be developed into gastronomic tourism through creativepreneurship in the form of gastronomic tour packages based on the behavior of Purworejo Regency tourists and the travel patterns of Purworejo Regency tourists.